EVALUASI PENGENDALIAN INTERN TERHADAP PROSEDUR PENGELUARAN KAS (PAYMENT) DI PT. X INDONESIA - Husna, Mila Mardia; Triyuwono, Iwan (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to evaluate whether PT. X Indonesia has implemented internal control for payments adequately. The evaluation was performed with a qualitative approach through observation and testing on payment procedures and internal control environment, in consideration of the best practices of internal control which includes sufficient segregation of duties, proper authorization, adequate documents and records, physical control over assets and records, and independent and periodic review. The results showed that PT. X Indonesia has segregated the duties of each job function clearly, implemented proper authorization system, held adequate documents and records, implemented physical control to protect company’s assets and records, and conducted independent review periodically. To conclude, PT. X Indonesia has implemented internal control for payments adequately.Keywords: Internal control, payment procedure, best practices, PT. X Indonesia.